The Future of Pentecostalism in the United States - Patterson, Eric.; Rybarczyk, Edmund (Lanham : Lexington Books, 2007)
This book considers whether Pentecostalism will remain a vibrant religious force in the land of its birth (the U.S.), and if so, what forms it will take. The contributors represent a variety of disciplinary and methodological approaches in answering these questions, often concluding that U.S. Pentecostalism(s) are in decline but able to reform.
Chapter 11 ""Follow Peace With All:"" Future Trajectories of the Church of God in Christ David D. Daniels, IIIChapter 12 Conclusion: Back to the Future? U.S. Pentecostalism in the 21st Century Eric Patterson; Select Bibliography; Index; About the Contributors.
Description based on print version record.
Keywords: Pentecostal churches -- United States; Pentecostalism -- United States; Pentecostalism -- United States; Pentecostal churches -- United States; RELIGION / Christianity / History; Electronic books